Targeted Degradation of PARP14 Using a Heterobifunctional Small Molecule. (4th May 2021) - Wigle, Tim J.; Ren, Yue; Molina, Jennifer R.; Blackwell, Danielle J.; Schenkel, Laurie B.; Swinger, Kerren K.; Kuplast‐Barr, Kristy; Majer, Christina R.; Church, W. David; Lu, Alvin Z.; Mo, Jason; Abo, Ryan; et al.
Abstract: PARP14 is an interferon‐stimulated gene that is overexpressed in multiple tumor types, influencing pro‐tumor macrophage polarization as well as suppressing the antitumor inflammation response by modulating IFN‐γ and IL‐4 signaling. PARP14 is a 203 kDa protein that possesses a catalytic domain responsible for the transfer of mono‐ADP‐ribose to its substrates. PARP14 also contains three macrodomains and a WWE domain which are binding modules for mono‐ADP‐ribose and poly‐ADP‐ribose, respectively, in addition to two RNA recognition motifs. Catalytic inhibitors of PARP14 have been shown to reverse IL‐4 driven pro‐tumor gene expression in macrophages, however it is not clear what roles the non‐enzymatic biomolecular recognition motifs play in PARP14‐driven immunology and inflammation. To further understand this, we have discovered a heterobifunctional small molecule designed based on a catalytic inhibitor of PARP14 that binds in the enzyme's NAD + ‐binding site and recruits cereblon to ubiquitinate it and selectively target it for degradation. Abstract : A tool to dissect PARP14 : A heterobifunctional small molecule that selectively degrades PARP14 is described. It can be used in studies to unravel the biological function of this large protein's mono‐ADP‐ribosyltransferase catalytic domain and its macrodomains, WWE domain and RNA recognition motifs in immunity and inflammation.